Knowledge, barriers and perceived needs of adolescent sexual and reproductive health services among higher secondary school students in Chitwan district (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Adolescent is a unique and formative time which goes through the physical, emotional and social change including exposure to health issues like sexually transmitted infection, unwanted pregnancy and unsafe abortion. Hence, the study aims to find out the knowledge, perceived needs and barriers related to adolescent sexual and reproductive health services (ASRHS).Methods: A cross-sectional study was conducted among 1352 adolescents of higher secondary schools located in Bharatpur Metropolitan city of Nepal. Self-administered questionnaire method was used to collect the data on knowledge, perceived need and barrier on adolescent sexual and reproductive health services. Descriptive and inferential analysis was performed to present the data.Results: Of total, only 14.6% of the adolescents had good knowledge on the sexual and reproductive health. The perceived need for the sexual and reproductive health service was 65.4% among the adolescents while only 18.3% utilized the service to fulfill the felt need. Shyness (41.3%), communication barrier (40.3%) and lack of confidentiality (38%) were the major barriers perceived by the adolescent for taking services. The knowledge level and felt need of ASRHS, both, significantly varied as per sex, grade and academic discipline of students.Conclusions: Knowledge level on adolescent sexual and reproductive health service was low while the perceived need was high and the knowledge and perceived need differ significantly by sex, grade and academic discipline of students.